FAKTOR FAKTOR YANG MEMENGARUHI STRUKTUR MODAL PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI - Gabriela, Jane; Jonnardi, Jonnardi (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This study aimed to examine the influence of profitability, asset structure, and liquidity toward capital structure on consumer goods industry sector companies listed in the Indonesia Stock Exchange for the 2016-2020 period. Sample was selected by using simple random sampling method. The number of samples are 36 companies over the past five years, there are 180 samples. Data processing techniques using multiple regression analysis what helped by EViews 10 and Microsoft Excel 2013. The results of this study conclude that the profitability have no effect on capital structure. Asset structure have effect on capital structure positively and liquidity have effect on capital structure negatively. The implication of this study is the need to increase asset structure that will increase capital structure which will bring a good signal for investors.